Boris Samuel, La production macroéconomique du réel. Formalités et pouvoir au Burkina Faso, en Mauritanie et en Guadeloupe - Boris Samuel (Revue de la Régulation)
This thesis examines the exercise of power and its transformations, based on the observation of concrete operations of macroeconomic management in two African countries, Burkina Faso and Mauritania, and one Caribbean territory, Guadeloupe. Its approach involves a combination of anthropology, the sociology of quantification and the historical sociology of the political.In all three cases studied, the detailed observation of macroeconomic calculation shows that the technocratic ethos is crucial for an understanding of the exercise of power. Social and political struggles over education and the high cost of living, and debates on the illusory claims of reformism, place the numerical approach at the very heart of social and political relations. On the turbulent political scene in Mauritania, Guadeloupe and Burkina Faso, the objects of economic management are at work, guiding the actions of individuals and provoking protest. Indeed, macroeconomics is not just to be found in the office: it is part of the political repertoire of ordinary people. It is rooted both in the specific history of these societies and in the autonomous logics of technique and procedure.